Natural regeneration capacity of the mangrove forest of Tortuga Estuary, Osa, Puntarenas, Costa Rica. - Vargas-Fonseca, Elena (Revista de Biología Tropical, 2015)
The study was conducted from February 2011 to January 2012, in the mangrove forest of Tortuga Estuary. A total of six parcels, each measuring 9m2, were established in the area, to evaluate the survival and growth rates of the mangrove seedlings. By the end of the study all parcels presented 100% mortality, indicating that the area is not recruiting young trees and therefore is not regenerating naturally. The results of this study suggest that the low salinity of the water table and the high rate of deposition of sediments, are the causes of the low survival rate of the seedlings and could also be affecting the adult individuals. The adult trees presented deteriorated health signs such as decomposition of their stilt roots and total loss of foliage. The borders of this ecosystem were georeferenced and compared with the official map that declares the Natural Patrimony of the Country, to determine areas that should be protected under this category. In general the mangrove forest of this estuary can be divided in two zones: the first one is characterized by a mature forest of mainly two species: Rhizophora racemosa (G. Mey.) and Pelliciera rhizophorae (Triana & Planch.). The second one is located in the banks of sand of the estuary, where the dominant specie is Laguncularia racemosa (C.F. Gaertn) in young stages. Both of these areas include mangrove ecosystems that are not included in the Natural Patrimony category.